Timing crisis information release via television - Wei, J.; Zhao, D.; Yang, F.; Du, S.; Marinova, Dora (Wiley-Blackwell Publishing Ltd., 2010)
When and how often to release information on television are important issues in crisis and emergency risk communication. There is a lot of crisis information, including warnings and news, to which people should have access, but most of it is not significantly urgent to interrupt the broadcasting of television programmes. Hence, the right timing for the release of crisis information should be selected based on the importance of the crisis and any associated communication requirements. Using recursive methods, this paper builds an audience coverage model of crisis information release. Based on 2007 Household Using TV (HUT) data for Hefei City, China, the optimal combination of broadcasting sequence (with frequencies between one and eight times) is obtained using the implicit enumeration method. The developed model is applicable to effective transmission of crisis information, with the aim of reducing interference with the normal television transmission process and decreasing the psychological effect on audiences. The same model can be employed for other purposes, such as news coverage and weather and road information.